Value-Based Care for Musculoskeletal Pain: Are Physical Therapists Ready to Deliver?. Issue 4 (25th November 2019) - Lentz, Trevor A; Goode, Adam P; Thigpen, Charles A; George, Steven Z
Abstract: Early physical therapy models hold great promise for delivering high-value care for individuals with musculoskeletal pain. However, existing physical therapist practice and research standards are misaligned with value-based principles, which limits the potential for growth and sustainability of these models. This Perspective describes how the value proposition of early physical therapy can be improved by redefining harm, embracing a prognostic approach to clinical decision making, and advocating for system-wide guideline-adherent pain care. It also outlines the need to adopt a common language to describe these models and embrace new, rigorous study designs and analytical approaches to better understand where and how early physical therapy delivers value. The goal is to define a clear path forward to ensure physical therapists are aligned within health care systems to deliver on the American Physical Therapy Association's vision of high-value care in a rapidly changing health care environment.